2019
DOI: 10.1039/c8tc05677c
|View full text |Cite
|
Sign up to set email alerts
|

Trap-induced conversion from singlet fission to intersystem crossing via in situ heating of rubrene-based organic light-emitting diodes

Abstract: An in situ heating method was used to investigate the effect of high temperature on the magneto-electroluminescence (MEL) of rubrene-based organic light-emitting diodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…Park et al found that after 60–80 °C thermal annealing, amorphous rubrene transformed into crystalline domains, forming disk-shaped aggregates with hundreds of micrometer diameter and roughness of approximate 10 nm. Lin et al annealed a rubrene/C 60 bilayer to shift the charge transfer state which benefited triplet exciton harvesting . Interestingly, rubrene films can be grown either in the bulk crystalline phase or with very low short-range order by molecular beam epitaxy. , The ability to produce different packing motifs using the same molecule presents an opportunity to study how the morphology of rubrene influences the exciton dynamics and SF, both of which will impact the eventual device performances …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al found that after 60–80 °C thermal annealing, amorphous rubrene transformed into crystalline domains, forming disk-shaped aggregates with hundreds of micrometer diameter and roughness of approximate 10 nm. Lin et al annealed a rubrene/C 60 bilayer to shift the charge transfer state which benefited triplet exciton harvesting . Interestingly, rubrene films can be grown either in the bulk crystalline phase or with very low short-range order by molecular beam epitaxy. , The ability to produce different packing motifs using the same molecule presents an opportunity to study how the morphology of rubrene influences the exciton dynamics and SF, both of which will impact the eventual device performances …”
Section: Introductionmentioning
confidence: 99%
“…23,24 The ability to produce different packing motifs using the same molecule presents an opportunity to study how the morphology of rubrene influences the exciton dynamics and SF, both of which will impact the eventual device performances. 25 In most cases, the photophysical behavior of a sample should be determined by purely local molecular interactions on length scales much less than 5 nm, so we would not expect different film thicknesses to affect the excited state dynamics. In this paper, we tested this assumption by investigating the exciton dynamics of ordinary amorphous rubrene thin films with various thicknesses (5−100 nm) which were deposited by using thermal evaporation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…式中, EL(B)和EL(0)分别表示器件在有、无外加磁场 时的发光强度 [20] . 一般来讲, 不同的激子演化过程具 有不同的MEL特征曲线, 它们可以作为一种高效率、 高灵敏性、无损非接触的探测手段探究有机半导体内 部的微观机制 [21,22] .…”
Section: 引言unclassified
“…红荧烯 (5,6,11,12- [10,22,23] . 我们对这种器件在低温和室温下的激子相 关演化过程及其MEL特征了解得比较全面 [8][9][10][11][12] [22,24] . 通过观察器件的表 面形貌, 证明了高温环境下器件中Rubrene薄膜确实产 生了结构缺陷.…”
Section: 引言unclassified
“…4,5 These changes are difficult to monitor in real-time operation and may directly or indirectly affect exciton interactions that ultimately affect device performance. 6 Little has been reported on microscopic OLED mechanisms at high temperatures.…”
Section: Introductionmentioning
confidence: 99%